SPIRITUAL BASE OF PESANTREN FOR BUILDING MULTICULTURAL AWARENESS IN INDONESIA CONTEXT - Mashuri, Saepudin; Futaqi, Sauqi; Sulhan, Ahmad (Islam Futura, 2024)
This study examines the spiritual base of Pesantren, which is essential in building multicultural awareness. In Indonesia, Pesantren is an Islamic religious education institution emphasizing spirituality's importance. Pesantren is also closely related to various social and religious aspects. This study aims to find a spiritual base and its utilization in building multicultural awareness. This research uses a phenomenological qualitative study with data collection through observation, interviews, and documentation. The research was conducted for 1.5 years, from 2018-2019. Observations were made for a week every month. Interviews were conducted with 16 informants at site A and 13 at site B. Data analysis used a constant comparative model. From the results of the study, there are several significant findings: 1) Kiai's view of the spirituality of Islamic boarding schools related to multiculturalism is based on the monotheism of humanity; 2) Pesantrens have spiritual capital that comes from Sufistic teachings (Sufism) and interacts spirally with multiculturalism; 3) multicultural values are born from spiritual values that are grown and summarised in three categories of values, namely fundamental values, personal values , and social values; and 4) spiritual-multicultural interactions that continue to make students more multicultural competent. Multicultural awareness built through intense spirituality can birth "selfless multiculturalism"; an authentic multicultural attitude.